1965
DOI: 10.1002/aic.690110609
|View full text |Cite
|
Sign up to set email alerts
|

Flow behavior of viscoelastic fluids in the inlet region of a channel

Abstract: The behavior of viscoelastic fluids in the inlet region of a channel formed by two parallel flat plates has been analyzed with a Rivlin-Ericksen approximation to describe the fluid properties. I t was found that viscoelasticity changed the entry length; both the magnitude and direction of this change were predicted to depend upon the detailed fluid properties. These predictions of the change in the entry length were seen to find some qualitative support in available experimental evidence.The directions for fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

1966
1966
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 46 publications
0
16
0
1
Order By: Relevance
“…DOI The rheology of polymeric fluids is often complex, and their material properties have a strong impact on flow behavior. It has long been observed that the presence of polymer molecules in a fluid can lead to flow instabilities and nonlinear dynamics [1][2][3][4][5][6][7]. For example, Giesekus [3] observed a cellular instability of a non-Newtonian fluid in Taylor-Couette flows, analogous to the classical TaylorCouette instability of Newtonian fluids, but at very low Reynolds (Taylor) numbers.…”
mentioning
confidence: 99%
“…DOI The rheology of polymeric fluids is often complex, and their material properties have a strong impact on flow behavior. It has long been observed that the presence of polymer molecules in a fluid can lead to flow instabilities and nonlinear dynamics [1][2][3][4][5][6][7]. For example, Giesekus [3] observed a cellular instability of a non-Newtonian fluid in Taylor-Couette flows, analogous to the classical TaylorCouette instability of Newtonian fluids, but at very low Reynolds (Taylor) numbers.…”
mentioning
confidence: 99%
“…Assuming a mean jet velocity, and 95% relaxation of the initial stresses in the distributor, then eq. [9] becomes (16) 1.84 ~ ,~ (NDeb)g --lg [10] Using ~ ~--0.015, values for eq. [10] are given in table 3 and for polyox solutions of concentration ~ 0.25% a mean of about 0.13 occurs.…”
Section: Elastic 'Solid-like' Behaviour -The Deborah Numbermentioning
confidence: 99%
“…Ismail and Karim [22,23] and Oliver and Karim [24] showed that secondary flow enhanced heat transfer in flattened tubes. The flow properties could be described for various conditions and geometries, as illustrated by Metzner et al [25] and Metzner and White [26]. This current work deals with the heat transfer of dilute solutions of viscoelastic liquids in tubes that had been flattened between rollers to obtain tubes of different aspect ratios.…”
Section: Introductionmentioning
confidence: 98%